A causal investigation of soy isoflavone intake for primary prevention of post-menopausal breast cancer among Asian women - Rajaram, Nadia N. (2022)
The incidence of breast cancer is increasing at an alarming rate across Asia, by up to 6% annually, compared to near stable incidence rates in many Western countries. While selective oestrogen receptor modulators and aromatase inhibitors are actively being studied as chemoprevention among high-risk Caucasian women, the risks may outweigh the benefits among Asian women with lower population risk of breast cancer. Modifiable lifestyle targets for primary prevention have long been identified, such as post-menopausal obesity, alcohol intake, and hormone replacement therapy use, but these risk factors are less prevalent among women in Asian countries. There remains an urgent need to find primary prevention strategies that are low risk, acceptable, and effective for Asian women.